Accuracy of high-resolution ultrasound in carpal tunnel syndrome - Ivanoski, Slavcho; Bozhinovska Smicheska, Maja; Vasilevska Nikodinovska, Violeta (Georg Thieme Verlag KG, 2016)
Purpose: The aim of this study was to evaluate the diagnostic efficiency of high-resolution ultrasound in diagnosis of carpal tunnel syndrome compared to electromyography exam (EMG). Materials and methods: 36 wrists of 20 patients with EMG diagnosis of carpal tunnel syndrome were prospectively evaluated using high resolution ultrasound. 14 patients were female and 6 male. Control group consisted of 17 asymptomatic volunteers (34 wrists). Ultrasound exam was performed the same day right after the EMG, by a radiologist experienced in MSK ultrasound. High resolution linear transducer was used. The radiologist was blinded to EMG results. Ultrasound diagnostic criterion for carpal tunnel syndrome was cross section area of median nerve of 10 mm2 or more measured at proximal carpal tunnel (at the level of pisiform bone). Sensitivity, specificity and accuracy of the method were evaluated. Results: Majority of the patients, 80% had bilateral carpal tunnel syndrome. Ultrasound showed true positive finding in 31 of 36 cases of carpal tunnel identified by EMG. Sensitivity was 86.1%. Specificity was also high, 88.2%, 30 of 34 cases were correctly recognized as normal by ultrasound. Positive predictive value was 88.6%, and negative predictive value was 85.7%. Accuracy of the method was high, 87.1%. Conclusion: Ultrasound in comparison to EMG shows high sensitivity, specificity and accuracy in diagnosis of carpal tunnel syndrome. Due to its availability, easiness of use and cost of the exam it can be used as a reliable method of choice for quick and accurate evaluation of carpal tunnel syndrome.